Quantitative low-volume assay for simultaneous determination of fentanyl, norfentanyl, and minor metabolites in human plasma and urine by liquid chromatography—tandem mass spectrometry (LC-MS/MS) - Mahlke, Nina Sophia; Ziesenitz, Victoria C.; Mikus, Gerd; Skopp, Gisela (International journal of legal medicine, 2014)
A rapid and sensitive liquid chromatography/tandem mass spectrometric (LC-MS/MS) method for simultaneous quantification of fentanyl (F), norfentanyl (NF), despropionylfentanyl (DPF), and hydroxynorfentanyl (OHNF) in human plasma and urine specimens has been developed and validated according to international guidelines. Analytes were extracted from 250-μL plasma or urine by liquid-liquid extraction. OHNF in urine affords a second extraction step and analysis with a different column. Calibration curves in plasma were linear from 0.05-10 ng/mL for F, 0.07-0.5 ng/mL for NF, 0.02-1.0 ng/ml for DPF, and 0.67-3.0 ng/mL for OHNF; in urine, from 0.09-10.0, 0.17-50, 0.08-1.0, and 1.0-5.0 ng/mL for F, NF, DPF, and OHNF, respectively. Analytical bias and intra- and inter-assay imprecision were within ±15 % of target, except for OHNF in plasma and DPF in urine at the respective lower quality control level. All analytes were stable in processed samples when stored for 24 h at room temperature. Recoveries and process efficiencies were above 82.9 and 75.1 % for all analytes in plasma and urine. The low level of DPF in plasma indicated with a matrix effect of 71.3 % moderate ion suppression, all other analytes in plasma and urine showed no matrix effects. The lower limit of quantification (LOQ) in plasma was 0.05, 0.07, 0.02 and 0.67 ng/mL for F, NF, DPF, and OHNF, respectively. In urine, the LOQ of F, NF, DPF, and OHNF were 0.09, 0.17, 0.08, and 1.28 ng/mL, respectively. This assay has been applied to human specimens collected during a clinical drug-drug interaction study.
Gesehen am 24.07.2020